2013
DOI: 10.1111/jcmm.12188
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C suppresses cell death in MCF‐7 human breast cancer cells induced by tamoxifen

Abstract: Vitamin C is generally thought to enhance immunity and is widely taken as a supplement especially during cancer treatment. Tamoxifen (TAM) has both cytostatic and cytotoxic properties for breast cancer. TAM engaged mitochondrial oestrogen receptor beta in MCF-7 cells and induces apoptosis by activation of pro-caspase-8 followed by downstream events, including an increase in reactive oxygen species and the release of pro-apoptotic factors from the mitochondria. In addition to that, TAM binds with high affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 42 publications
2
37
0
2
Order By: Relevance
“…5F, Supporting Information and Table 3) left 42 ± 5% and 59 ± 3% of cells viable respectively. Again, this shows that the presence of ascorbic acid in SWCNTs reduces its photothermal effect on MCF-7 cancer cells and the finding from this work supported the earlier report by Subramani et al [24] which stated that AA suppresses cell death induced by tamoxifen in MCF-7 human breast cancer cells. The ability of ascorbic acid in suppressing cell death might be due to their ability to reduce oxidative DNA damage and its role in cell differentiation [68].…”
Section: Phototoxicity Of Swcnts Swcnt-aa and Znmcppc Derivativessupporting
confidence: 94%
See 1 more Smart Citation
“…5F, Supporting Information and Table 3) left 42 ± 5% and 59 ± 3% of cells viable respectively. Again, this shows that the presence of ascorbic acid in SWCNTs reduces its photothermal effect on MCF-7 cancer cells and the finding from this work supported the earlier report by Subramani et al [24] which stated that AA suppresses cell death induced by tamoxifen in MCF-7 human breast cancer cells. The ability of ascorbic acid in suppressing cell death might be due to their ability to reduce oxidative DNA damage and its role in cell differentiation [68].…”
Section: Phototoxicity Of Swcnts Swcnt-aa and Znmcppc Derivativessupporting
confidence: 94%
“…In addition, the intravenous administration of ascorbate in pharmacological concentrations can selectively kill cancer cells [19][20][21][22] due to its ability to generate hydrogen peroxide (H 2 O 2 ) that can further produce free radicals. However, there have been conflicting reports on the role of AA in cancer therapeutics; Kurbacher et al [23] reported that AA improves the anti-neoplastic activity of doxorubicin, cisplatin, and paclitaxel in human breast cancer cells in vitro while studies by Subramani et al [24] stated that AA suppresses cell death in MCF-7 human breast cancer cells induced by tamoxifen. Ascorbic acid is a well-known antioxidant and would be expected to quench singlet oxygen and other ROS required for PDT.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 97%
“…In vitro studies with human MCF-7, AA exposure causes attenuation of antineoplastic activity and may affect the therapeutic response [15]. There are also reports indicating that AA can enhance the effectiveness of chemotherapeutic agents that can reduce the cytotoxicity of anticancer drugs, and also may prevent free radicals and neutralize some carcinogens [14,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of human MCF-7, vitamin C exposure causes attenuation of antineoplastic, it may affect the therapeutic response [15]. There are also reports that indicate high doses of ascorbic acid, increasing apoptosis in Sarcoma 180 cells on mice co-treated with paclitaxel, enhancing the effects of anticancer [20].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation